BRI FINANCIAL PERFORMANCE ANALYSIS USING PROFITABILITY AND SOLVENCY RATIO POST COVID 2021-2023 - Rika Amalia; Romy Nugraha; Ari Ayu (Universitas Ichsan Sidenreng Rappang, 2024)
This study aims to determine the financial performance of PT. Bank Rakyat Indonesia after Covid whether it is healthy and analyzed using profitability and solvency ratios. The method used is quantitative descriptive and the data collection technique is documentation technique. The population used in this study is all financial reports of PT. Bank Rakyat Indonesia listed on the Indonesian Stock Exchange and the sampling technique used is the purposive sampling method. The results of the study show the financial performance of PT. Bank Rakyat Indonesia (Persero) Tbk for the period 2021-2023 based on the solvency ratio measured by the Capital Adequacy Ratio, the results of the analysis fluctuate because risk-weighted assets fluctuate and are not balanced by capital growth. Financial performance based on the results of the profitability ratio analysis measured by Return On Asset shows a very healthy condition because it is able to continue to increase assets, the results of the Return On Equity analysis in 2021 are less healthy but in 2022-2023 it has started to improve and based on the results of the Net Profit Margin analysis shows a very healthy condition because the company is able to increase net profit every year.